Long-term efficacy and tolerability of add-on pioglitazone therapy to failing monotherapy compared with addition of gliclazide or metformin in patients with type 2 diabetes. - Charbonnel, B; Schernthaner, G; Brunetti, P; Matthews, DR; Urquhart, R; Tan, M; Hanefeld, M (2005)
AIMS/HYPOTHESIS: The aim of this analysis was to examine the long-term effects of pioglitazone or gliclazide addition to failing metformin monotherapy and pioglitazone or metformin addition to failing sulphonylurea monotherapy in patients with type 2 diabetes. METHODS: Two 2-year, randomised, multicentre trials were performed in patients with inadequately controlled type 2 diabetes (HbA1c 7.5-11% inclusive), who were receiving either metformin or a sulphonylurea at > or = 50% of the maximum recommended dose or at the maximum tolerated dose. In the first study, patients on metformin received add-on therapy with pioglitazone (15-45 mg/day, n = 317) or gliclazide (80-320 mg/day, n = 313). In the second study, patients on sulphonylurea therapy were randomised to receive add-on therapy with either pioglitazone (15-45 mg/day, n = 319) or metformin (850-2,550 mg/day, n = 320). HbA(1)c, fasting plasma glucose, insulin and lipids were investigated. RESULTS: At week 104, the mean reduction from baseline in HbA(1)c was 0.89% for pioglitazone and 0.77% for gliclazide addition to metformin (p = 0.200). There was a statistically significant between-group difference for the change in mean fasting plasma glucose at week 104 (-1.8 mmol/l for pioglitazone vs -1.1 mmol/l for gliclazide, p < 0.001). There were no significant differences in changes from baseline in glycaemic parameters for pioglitazone compared with metformin addition to sulphonylurea therapy. Whether added to metformin or sulphonylurea, pioglitazone caused significantly greater decreases in triglycerides and significantly greater increases in HDL cholesterol than the comparator regimens (p < or = 0.001). There were decreases in LDL cholesterol in the comparator groups and these were significantly different from the small changes observed with pioglitazone (p < 0.001). All treatment regimens were well tolerated. There were weight increases of 2.5 kg and 3.7 kg in the pioglitazone and 1.2 kg in the gliclazide add-on groups, and there was a mean decrease of 1.7 kg in the metformin add-on group. CONCLUSIONS/INTERPRETATION: As add-on therapy to existing sulphonylurea or metformin therapy, pioglitazone improved glycaemic control and this improvement was sustained over 2 years. Furthermore, there were potential benefits in terms of improvements in specific lipid abnormalities. This could offer an advantage over the addition of other oral agents in the long-term treatment of diabetes.